Modeliranje izgube uporabnosti in ocena navidezne starosti asfaltnih vozišč na osnovi vizualne ocene stanja - Pavšič, Primož (Gradbeni vestnik, 2022)
Under the influence of traffic load and environmental conditions, pavements continuously deteriorate. Using the modified Swiss index (MSI), we can assess and monitor pavement aging, while its functionality can be defined by the loss of serviceability. The article presents a proposed new model function for describing pavement aging or loss of serviceability with the assessment of the pavement condition using MSI and the determination of the apparent pavement age, based on the proposed model of pavement aging.
Keywords: condition assessment; model; MSI; ocena stanja; odprti dostop; open access; pavement; vozišče